2021
DOI: 10.1175/jcli-d-20-0909.1
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Cycle of Tropical Oceanic Mesoscale Cold Pools

Abstract: Tropical convection regimes range from deep organized to shallow convective systems. Mesoscale processes such as cold pools within tropical convective systems can play a significant role in the evolution of convection over land and open ocean. Although cold pools are widely observed, their diurnal properties are not well understood over tropical oceans and land. The oceanic cold pool identification metric applied herein uses the gradient feature (GF) technique and is compared with diurnally-resolved buoy-ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 85 publications
4
7
0
Order By: Relevance
“…This afternoon peak in the frequency of cold pools is also found by Garg et al. (2021) based on their cold pools that are identified from buoys in global ocean basins.…”
Section: Methodssupporting
confidence: 81%
See 1 more Smart Citation
“…This afternoon peak in the frequency of cold pools is also found by Garg et al. (2021) based on their cold pools that are identified from buoys in global ocean basins.…”
Section: Methodssupporting
confidence: 81%
“…In fact, we find that the frequency and magnitude of cold pools are higher during the day than at night at Addu Atoll (not shown). This afternoon peak in the frequency of cold pools is also found by Garg et al (2021) based on their cold pools that are identified from buoys in global ocean basins.…”
Section: Cold Pool Identificationsupporting
confidence: 59%
“…In the evening, the cold pool reached close to the coast and travelled along the southeast coast. In a recent study by Garg et al (2021), small cold pools were associated with shallower convection due to relatively drier environmental conditions (less total column water vapour). In view of the drier conditions over the southeast coast as well as the predominant stratiform precipitation type, we can expect a small cold pool to form over these regions in India.…”
Section: Discussionmentioning
confidence: 90%
“…In view of the drier conditions over the southeast coast as well as the predominant stratiform precipitation type, we can expect a small cold pool to form over these regions in India. Thus, the nocturnal precipitation peak offshore of the southeast coast may be related to cold pool movement under the mean environmental flow and their interactions (e.g., Garg et al, 2021; Ruppert & Hohenegger, 2018); however, further research is needed to explain how cold pools interact in this region.…”
Section: Discussionmentioning
confidence: 99%
“…Cold pools occur when evaporatively‐cooled air sinks to the surface and expands horizontally in all directions, resulting in local air temperature and moisture fronts that alter the surrounding environment (Betts & Silva Dias, 1979; Fournier & Haerter, 2019; Glickman & Zenk, 2000; Haerter & Schlemmer, 2018; Lafore & Moncrieff, 1989; Rochetin et al., 2021; Tompkins, 2001). These frontal regions are also accompanied by large variations in wind speed (i.e., the “gust” front) that drive air‐sea fluxes, or surface exchanges of energy between the ocean and the atmosphere (Garg et al., 2020, 2021; Grant & van den Heever, 2016; Gentine et al., 2016; Langhans & Romps, 2015; Ross et al., 2004; Saxen & Rutledge, 1998; Skyllingstad & de Szoeke, 2015; Young et al., 1995).…”
Section: Introductionmentioning
confidence: 99%